Risk factors for pharmacotherapy for storage symptoms after transurethral resection of the prostate in patients with benign prostatic hyperplasia. Issue 5 (21st March 2022) - Tsai, Cheng‐Han; Fan, Yu‐Hua; Lin, Alex T. L.; Huang, William J.
Abstract: Objectives: Postoperative persistence of storage symptoms after transurethral resection of the prostate (TURP) is bothersome, and evidence of its cause is sparse. We sought to analyze risk factors for using antimuscarinics or beta‐3 agonists after TURP in benign prostatic hyperplasia (BPH) patients. Methods: BPH patients who underwent TURP and were followed up for >6 months after surgery were retrospectively enrolled. Postoperative pharmacotherapy for storage symptoms was defined as the prescription of antimuscarinics or beta‐3 agonists within 3 months after TURP for >3 months. Preoperative and perioperative variables were evaluated for their effect on the postoperative prescription of antimuscarinics or beta‐3 agonists. Results: Of the 376 patients, 45 (12.0%) received postoperative pharmacotherapy for storage symptoms. Patients who underwent bipolar TURP were significantly more likely to receive postoperative pharmacotherapy than those who underwent monopolar TURP (15.7% vs 6.9%; P  = 0.01). Significantly more patients with intravesical prostatic protrusions >1 cm used postoperative pharmacotherapy than those with protrusions of ≤1 cm (14.4% vs 5.2% respectively; P  = 0.02). Multivariate logistic regression analysis revealed age >75 years (odds ratio [OR] 3.04; 95% CI 1.29‐7.16; P  = 0.011), intravesical prostatic protrusion >1 cm (OR, 3.48; 95% CI, 1.32‐9.15; P  = 0.012), and bipolar transurethral resection (OR 4.25; 95% CI 1.53‐11.80; P  = 0.005) as significant risk factors for postoperative pharmacotherapy. Conclusions: Advanced age, intravesical prostatic protrusion, and bipolar TURP were significantly associated with postoperative pharmacotherapy for storage symptoms after TURP in BPH patients. Therefore, patients with these risk factors might be informed about the risk of postoperative storage symptoms that may require medications after TURP.